Activation of vibrational-induced CO2 dissociation in cold non-equilibrium plasma. (3rd March 2023) - Pietanza, Lucia Daniela; Colonna, Gianpiero; Capitelli, Mario
Abstract: The activation of vibrational-induced dissociation of CO2 in cold non-equilibrium plasma discharges is investigated by means of a 0D self-consistent kinetic model, which, with a state-to-state approach, is able to calculate the CO2 vibrational distribution function (vdf) of the asymmetric mode levels, the electron energy distribution function and the corresponding vibrational-induced and electron impact CO2 dissociation rates. The conditions for the onset of such activation are linked to the achievement of a sufficiently high CO2 vibrational excitation characterized by the presence of a non-equilibrium plateau in the CO2 vdf, resulting from the combined effect of electron–vibrational and vibrational–vibrational collisions, which, by overpopulating the higher vibrational levels, enhances dissociation. Such non-equilibrium conditions are maximized at lower gas temperature, lower pressure and higher power density values. In particular, for the power density, an activation threshold value can be obtained from simulations and its dependence on the gas temperature and pressure can be investigated. The dependence of the maximum vibrational temperature reached at the end of the discharge as a function of the gas temperature and pressure is also analyzed. A satisfactory agreement from our simulation results with the Kotov's criterion for vibrational activation has been found.